Effect of Two Specialty Corn Protein-Based Products on Growth Performance and Fecal Dry Matter in Nursery Pigs - Tomas Porcel de Peralta; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt; Julia P. Holen; Haley Schwecke; Alyssa M. Betlac; Keith Mertz; John F. Patience (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 4,100 weanling pigs (initially 12.9 ± 0.13 lb) were used in a 42-d study to determine the effect of two specialty corn protein products, Modified Corn Protein (MCP) and MOTIV (Cargill Starches, Sweeteners, & Texturizers, Blair, Nebraska), on growth performance and fecal dry matter (DM). At approximately 23 d of age, pigs were weaned and randomly placed in pens. Pens of pigs were then blocked by average pen weight and randomly allotted to one of four dietary treatments in a randomized complete block design with 50 and 52 pigs per pen and 20 replicate pens per treatment. The first dietary treatment contained 3.5% fish meal and 7.5% enzymatically treated SBM in phase 1 and 5% enzymatically treated SBM in phase 2 (high complexity). The second diet contained 5% enzymatically treated SBM, no fishmeal in phase 1 and 2.5% enzymatically treated SBM in phase 2 (medium complexity). This treatment diet contained approximately 6 and 3% more conventional SBM in phases 1 and 2 respectively than the high complexity diet. The final two treatment diets did not contain fishmeal or enzymatically treated SBM in phases 1 or 2, and those treatments were replaced by either 10% MCP or MOTIV in phase 1 and 5% in phase 2. The amount of L-Lys HCl was adjusted to achieve a similar level of conventional SBM as the high complexity diet in both phases. Diets were fed in three phases based on a feed budget with 4 and 12 lb/pig for phases 1 and 2, respectively. Phase 3 was a common diet fed to all pigs for the remainder of the study. Overall, pigs fed the medium complexity diets had a greater (P < 0.05) ADG and d 42 BW compared with pigs fed diets with MOTIV, while pigs fed the high complexity diets and those fed MCP intermediate diets showed intermediate results. Average daily feed intake was greater (P < 0.05) for pigs fed medium complexity diets compared with pigs fed diets containing MCP and MOTIV, while pigs fed high complexity diets were intermediate. No differences were observed for F/G among treatments. For fecal DM, pigs fed diets with MOTIV had increased (P < 0.05) fecal DM, compared to pigs fed medium complexity diets, with those fed the high complexity or MCP diets intermediate. There was no treatment effect on mortality or removals. In conclusion, the specialty corn protein products tested in this trial decreased ADG and ADFI in early nursery, which carried over to the overall performance. Additionally, increasing diet complexity in phase 1 and 2 diets did not improve performance compared to diets formulated to medium complexity.
Keywords: corn protein; growth performance; nursery pigs; fecal dry matter